Management of Acid Rock Drainage Based on Geochemical Characterisation of Waste Rock Material, Study Case: Gold Mining With High Sulfidation Ephithermal (HS) Deposits - Fakhrur Razi; Titah, Harmin S. (UIR PRESS, 2024)
Acid rock drainage (ARD) or Acid mine drainage (AMD) is significant challenge for the global gold mining industry, necessitating specialized treatment to prevent its occurrence. Rambajoring is deposits located at the North Sumatra Martabe gold mine, the mine is an epithermal deposit of a high sulfidation system. A crucial step in management of AMD is identifying rocks that potentially produced acid water or not if contact with water and oxygen. Static testing provides an indication of the potential acidity that can be generated by rock samples based on their composition. These rocks are classified into Potentially Acid Forming (PAF) or Non-Acid Forming (NAF). Laboratory analyses including Acid Base Accounting (ABA), Net Acid Generating (NAG) Test, and paste pH, identified all lithology with uncertain category. This uncertainty occurs impact of presence of significant non-pyritic or non-acid forming sulfide sulphur mineral in this case of Alunite (KAl3SO2OH6) minerals. Containing these minerals will result in erroneously high estimations of total sulphur (S) and increasing the calculated of NAPP. Long term implication non-pyritic sulfide may oxidize slowly, leading to delayed acid generation not reflected in static NAPP calculation. Supplementary test to validation static test result and analysis geochemical behaviour of rocks using kinetic testing with Field Column Leach Test (FCLT) method. FDCLT test confirm in eight months period monitoring, all lithology have a lag time before significant acidity is produced and classified as PAF rocks. The leaching properties of material had highest concentrations of iron (Fe), cooper (Cu) and zinc (Zn). Keyword : AMD, ABA, Geochemical Characteristics, NAF, PAF, Kinetic Test, Static Test